1995
DOI: 10.1046/j.1468-2982.1995.015002147.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Trigeminal Evoked Potentials: Normative Aging Data

Abstract: A mild electric shock applied to the lower lip was used to elicit reliable evoked potentials from the trigeminal nerve in 50 normal adults who ranged in age from 20 to 69 years. The waveforms were morphologically similar to those observed with invasive procedures. No substantial effects for subject age, side of stimulation, or recording electrode were obtained for any of the individual trigeminal evoked potential amplitudes or latencies. Female subjects tended to have somewhat larger amplitudes and shorter lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…This has not been reported in other studies. In contrast, in one study investigating the influence of age, sex and stimulation side on TSEP latencies, no substantial effects were found for subject age (n=50) (22). These different findings can not be readily explained, as the methodology used in that publication differs only slightly from ours.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This has not been reported in other studies. In contrast, in one study investigating the influence of age, sex and stimulation side on TSEP latencies, no substantial effects were found for subject age (n=50) (22). These different findings can not be readily explained, as the methodology used in that publication differs only slightly from ours.…”
Section: Discussioncontrasting
confidence: 72%
“…Drawbacks of these methods are that they may be painful and uncomfortable, and seem difficult to perform repeatedly in an out-patient clinic setting. Some authors searched for consistent and comparable responses, using a non-invasive technique, while avoiding muscle artefacts (22). As advised by Findler and Feinsod, we reversed the stimulus polarity after half of the stimulations, which indeed minimized the stimulus artefact (9, 16, 21).…”
Section: Discussionmentioning
confidence: 99%
“…However, the discussion did not end with this study from 1987. In our present study (1) we followed more recently published methods on TSEPs, and found results consistent with those studies (2, 3). In addition, we wholeheartedly agree that laser-evoked potentials may be useful in the assessment of unmyelinated trigeminal pathways (4).…”
supporting
confidence: 90%
“…It is also difficult to establish age-matched controls since those after the fifties usually take medications for another health condition. However, these criteria are not necessary because EP waveforms tend to be remarkably stable within and across subject age in both amplitude and latency 41 .…”
Section: Discussionmentioning
confidence: 99%